Human induced pluripotent stem cell-derived dopaminergic neurons release alpha-synuclein through neuronal activity - Maierdanjiang Nuermaimaiti; Kei-ichi Ishikawa; Genko Oyama; Risa Nonaka; Takahiro Shiga; Takayuki Jo; Taiji Tsunemi; Ryota Nakamura; Rejko Krüger; Wado Akamatsu; Nobutaka Hattori (Neuroscience Research)
Lewy body diseases, including Parkinson's disease (PD), are characterized by the spread of alpha-synuclein (αSyn) between neurons across synapses, a process crucial for understanding their pathophysiology and developing effective treatments. In this study, we aimed to investigate the role of neuronal activity in releasing αSyn from human induced pluripotent stem cell-derived dopaminergic neurons. We examined human induced pluripotent stem cell-derived dopaminergic neurons, both healthy and those with the αSyn gene mutation associated with PD. We employed pharmacological agents and optogenetic techniques and demonstrated that increased neuronal activity, induced by bicuculline or optogenetic stimulation, significantly enhances αSyn release. However, suppression of neuronal activity with cyanquixaline reduces αSyn secretion. These findings underscore the pivotal role of neuronal activity in αSyn transmission between neurons, showing its potential impact on the spread of Lewy pathology in patients with neurodegenerative diseases like PD. Therefore, this study advances our understanding of PD and opens new avenues for therapeutic strategies to mitigate Lewy body disease progression.